Analisis pengaruh growth terhadap profit pada perusahaan manufaktur terbuka di Indonesia: Analisis model panel data dinamis - Prakasa, Aditya Guntur (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2019)
Growth will affect profitability of a firm. There is ongoing debate about how growth will affect profit both theoritically and empirical results. Classical hypothesis predict growth will affect profit positively. Growth can improve firm profitability because the effect from economies of scale and the learning curve effect that makes the production process and the cost of production become more efficient. Behavioral hypothesis predict growth will affect profit negatively because of principal agent problem, managerial constraints, penrose effect or diseconomies of scale. The objective of this study is to examine the effect of growth to profit based on the argument between Classical hypothesis and behavioral hypothesis. This study used dynamics panel data with generalized method of moments (GMM) as estimator. This study observed 82 publicly listed manufacturing firm in Indonesia consist of nine periods from 2009 to 2018 resulting in 656 observations. Empirical result shows that growth will affect profit negatively. Thus, prove the behavioral hypothesis that predict negative influence of growth to profit.